THE AVENGERS / 3 - Bendis, Brian Michael; Acuna, Daniel; Guedes, Renato (New York : Marvel, 2012)
The madness and drama of FEAR ITSELF has taken its toll on the mighty Avengers, and now they must reinvent themselves once more! The entire world awaits word of who will be the Avengers! Then: HAMMER returns! Witness the latest and greatest roster of Avengers in action as they root out the resurrected organization's secret labs! But who's really behind this latest threat, and who rebuilt the new Dark Avengers? And how can the Avengers battle the combined forces of Hydra, AIM, the Hand, and HAMMER - all under the leadership of Norman Osborn?
Contains material originally published in magazine form as Avengers #18-24 and 24.1.
Keywords: Avengers (Fictitious character) -- Comic books, strips, etc; Graphic novels